2022
DOI: 10.3389/fendo.2022.924952
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly and Colorectal Neoplasm: An Update

Abstract: Acromegaly is a systemic disease caused by excessive inappropriate secretion of GH and IGF-I levels, resulting in many systemic complications, including cardiovascular, respiratory, metabolic diseases, and a possible increased risk of some neoplasias. Although many studies on acromegaly and cancer remain uncertain, most data indicate that colorectal cancer (CRC) incidence is increased in this population. The exact mechanism involved in the role of GH-IGF-I axis in CRC has not been fully explained, yet it is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…The risk of colorectal cancer was moderately elevated in our cohort, consistent with many studies [ 38 ]. Most were diagnosed after acromegaly, even when the follow-up time was relatively short.…”
Section: Discussionsupporting
confidence: 92%
“…The risk of colorectal cancer was moderately elevated in our cohort, consistent with many studies [ 38 ]. Most were diagnosed after acromegaly, even when the follow-up time was relatively short.…”
Section: Discussionsupporting
confidence: 92%
“…The metabolic complications, including insulin resistance and diabetes mellitus, increase the risk of cardiovascular-related morbidity and mortality [ 1 , 6 ]. Further, increased levels of IGF-1 has been associated with increased risk for several malignancies [ 7 ], and studies have suggested GH and IGF-1 to facilitate a tumor microenvironment and neoplastic growth in the colon [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-215-5p is downregulated in colorectal cancer tissues, possibly acting as a tumor suppressor [ 96 ]. As patients with acromegaly have an increased colorectal cancer risk [ 4 , 97 ], miR-215-5p could be a target for further research in this context.…”
Section: Circulating Mirnas In Acromegalymentioning
confidence: 99%